Insertion of LINE-1 Retrotransposon Inducing Exon Inversion Causes a Rotor Syndrome Phenotype - Zhou, Donghu; Qi, Saiping; Zhang, Wei; Wu, Lina; Xu, Anjian; Li, Xiaojin; Zhang, Bei; Li, Yanmeng; Jia, Siyu; Wang, Hejing; Jia, Jidong; Ou, Xiaojuan; et al. (Frontiers in Genetics, 2020)
Rotor syndrome, a rare autosomal-recessive genetic disorder characterized by conjugated hyperbilirubinemia, is caused by biallelic pathogenic variants in both SLCO1B1 and SLCO1B3 genes. Long interspersed nuclear elements (LINEs) make up about 17% of the human genome and insertion of LINE-1 in genes can result in genetic diseases. In the current study, we examined SLCO1B1 and SLCO1B3 genes in two Chinese patients diagnosed with Rotor syndrome based on laboratory tests. In one patient, a novel exon 4 inversion variant was identified. This variant may have been induced by LINE-1 retrotransposon insertion into SLCO1B3 intron 3, and was identified using genome walking. Splicing assay results indicated that the exon inversion, resulting in SLCO1B3 exon 4 (122 bp) exclusion in the mature mRNA, might generate a premature termination codon. Here, we describe an exon inversion contributing to the molecular etiology of Rotor syndrome. Our results may inform future diagnoses and guide drug prescriptions and genetic counseling.